2021
DOI: 10.1371/journal.pone.0245909
|View full text |Cite
|
Sign up to set email alerts
|

A performance comparison of supervised machine learning models for Covid-19 tweets sentiment analysis

Abstract: The spread of Covid-19 has resulted in worldwide health concerns. Social media is increasingly used to share news and opinions about it. A realistic assessment of the situation is necessary to utilize resources optimally and appropriately. In this research, we perform Covid-19 tweets sentiment analysis using a supervised machine learning approach. Identification of Covid-19 sentiments from tweets would allow informed decisions for better handling the current pandemic situation. The used dataset is extracted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 237 publications
(155 citation statements)
references
References 51 publications
3
117
0
4
Order By: Relevance
“…The lexicon method integrates sentiment lexicons which are comprised of a set of rules for the classification of words from the text as positive, negative, or neutral [35]. The foundation of lexicon-based sentiment classification is that the polarity of a text can be decided using the polarity of sentimentbearing words in a given text.…”
Section: Lexicon-based Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lexicon method integrates sentiment lexicons which are comprised of a set of rules for the classification of words from the text as positive, negative, or neutral [35]. The foundation of lexicon-based sentiment classification is that the polarity of a text can be decided using the polarity of sentimentbearing words in a given text.…”
Section: Lexicon-based Methodsmentioning
confidence: 99%
“…The study suggested that 76% of the reviews were following the numeric rating whereas, 24% of the reviews and their corresponding numeric rating were not in correlation with each other. Along the same lines, [35] suggested that using TextBlob for sentiment analysis enhances the performance of models. In the light of the above discussion, we performed the self-annotation of the unannotated dataset using sentiment lexicons.…”
Section: A Dataset Descriptionmentioning
confidence: 95%
See 1 more Smart Citation
“…Numerous research groups have exploited the state-of-art of machine learning to catalog and analyze the large flows of COVID-19-related information circulating on social networks, forums, and online platforms like Twitter, Reddit, Instagram, Facebook, and YouTube ( Tsao et al, 2021 ). Among the most skillful approaches, Rustam et al adopted a wide variety of supervised algorithms such as random forest (RF), XGBoost classifier, support vector classifier (SVC), extra trees classifier (ETC), decision tree (DT), and long-short term memory (LSTM) deep learning model to analyze COVID-19-related tweets sentiment ( Rustam et al, 2021 ). Their results showed that: 1) Extra Trees Classifiers outperformed all other models by achieving a 0.93 accuracy score using the authors’ proposed concatenated features set; 2) the LSTM achieved low accuracy as compared to machine learning classifiers.…”
Section: Introductionmentioning
confidence: 99%
“…WSNs are deployed in diverse fields of appliances due to their low‐cost and easier deployment characteristics 5–7 . Its appliances are familiar in areas such as home security, railway monitoring, military supervision, smart buildings, and agricultural field, health care, and remote monitoring 8–11 . Nevertheless, there are certain challenges, which should be prevailed while designing the WSN for the next generation.…”
Section: Introductionmentioning
confidence: 99%